The Cult of Water in Turkish Belief Systems - SARITUNÇ, Berrin (International Journal of Scientific Research and Management (IJSRM), 2023)
In many belief systems throughout history, holiness has been attributed to the water element. In the Turkish belief system, too, water appears as a purifying element to which sacrifices are made, wishes are made, and the representative of abundance and fertility. In the sources, we see that the Turks prefer places close to water as their living space, and that water is the address of protection from evil and diseases, purification and cleaning, in short, healing. It is possible to see traces of the place of water among Turkish cultural codes in the first Turkish Islamic works, Dede Korkut stories, legends and travel books. When we look at the Turkish administrative system, while the Turkish khan and lords are responsible for protecting and watching over their people, water also protects the Turkish lords.On the other hand, it can be said that the main axis is formed around the water, from the fact that the new-born child has a healthy and beneficial long-lasting life in the transition period rituals in Anatolia, from the wish that the marriage will be prosperous when the bride pours water in a new marriage and the marriage will be fruitful, to the celebrations in the hidrellez around the water. In this study, the place and meaning of water in Turkish belief systems will be tried to be evaluated with examples.